sVCAM-1 as a Marker of Endothelial Dysfunction associated with Severe Course of a Novel Coronavirus Infection (COVID-19) - V. I. Podzolkov; A. E. Pokrovskaya; D. D. Vanina; I. I. Shvedov (Рациональная фармакотерапия в кардиологии, 2023)
Aim. To study the association of the level of endothelial dysfunction marker sVCAM-1 with the severe course of COVID-19.Material and methods. The study included 100 patients with COVID-19, who were divided into 3 groups depending on the degree of lung damage based on the results of computed tomography (CT): group CT 1 – 29 patients, group CT 2 – 61 patients and the group CT 3 – 10 patients. In addition to the standard examination performed for coronavirus infection, all patients underwent carotid Doppler ultrasound, analysis of arterial stiffness indices (CAVI, ABI) using the VaSera device, and evaluation of the plasma sVCAM-1 concentration by ELISA.Results. The plasma sVCAM-1 concentration was significantly higher in the groups of patients with moderately severe (CT 2) and severe (CT 3) lung lesions than in patients with mild lesions (CT 1). In the general group of patients significant correlations were found between the plasma sVCAM-1 concentration and the level of oxygen saturation (r=-0.39, p=0.032), hospital length of stay (r=0.24, p=0.026), values of C-reactive protein (r=0.25, p=0.042), ferritin (r=0.38, p=0.021), LDH (r=0.52, p=0.015) , as well as the percentage of pulmonary involvement according to CT data at admission (r=0.41, p=0.019) and on the day of discharge (r=0.35, p=0.022). According to multivariate regression analysis, sVCAM-1 does not depend upon gender, age, body mass index (BMI), the presence of type 2 diabetes mellitus (T2DM) and hypertension, and is a marker associated with cytokine storm progression, intermediate negative dynamics according to CT data, and need for respiratory support. The presence of type 2 diabetes, as well as elevated sVCAM-1 concentrations, is associated with an increased risk of high-dose glucocorticosteroid therapy. The threshold levels of this marker were calculated for each of the above events. We revealed a correlation between the sVCAM-1 concentration and the carotid intimal medial thickness in the general group of patients (r=0.25, p=0.036).Conclusion. An increase in the plasma sVCAM-1 concentration reflects the progression of endothelial dysfunction, one of the key factors in the pathogenesis of COVID-19. The latter necessitates the need for endothelium protective therapy for these patients. The evaluation of sVCAM-1 in blood plasma is a promising diagnostic technique aimed at predicting the risk of a severe course of COVID-19 and its long-term health hazards.